2001
DOI: 10.1080/714904371
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy: risk factors for adverse perinatal outcome

Abstract: Teenage pregnancy was found to be associated with adverse outcome such as LBW, preterm delivery, small for gestational age and malformations. The risk for LBW was affected mainly by demographic factors (maternal ethnicity, lack of prenatal care) and medical factors (pregnancy-induced hypertension, malformations).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 13 publications
11
55
1
1
Order By: Relevance
“…Most of the other studies present the same results, except some which reported increased incidence of infection, meconium aspirations and systemic malformations. 2,4,12 Increased incidence of fetal death, similar to the present one, had been reported by other studies also. 11,22,23 The limitation of this study is that it is a hospital-based study and therefore may not be a true reflection of the situation in the community.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most of the other studies present the same results, except some which reported increased incidence of infection, meconium aspirations and systemic malformations. 2,4,12 Increased incidence of fetal death, similar to the present one, had been reported by other studies also. 11,22,23 The limitation of this study is that it is a hospital-based study and therefore may not be a true reflection of the situation in the community.…”
Section: Discussionsupporting
confidence: 89%
“…6,10 However, other investigators have observed no difference in various age groups. 4,8,9,11 Younger mothers were found to be worst affected. Regarding the mode of delivery, difference in observations is present.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Teenage parenthood has been associated with higher incidence rates of a variety of prenatal and perinatal conditions including small for gestational age, preterm delivery, low birth weight, birth defects, and sudden infant death syndrome (Gortzak-Uzan et al 2001). In addition, teen mothers are more likely to have infants that are born with infections and/or chemical dependence due to maternal substance abuse (Gilbert et al 2004;MalamitsiPuchner and Boutsikou 2006;Menacker et al 2004).…”
Section: The Effects Of Teen Repeat Births On Child Health and Develomentioning
confidence: 98%
“…Pregnant teenagers are high-risk gynecological cases with possibilities of low birth weight, preterm delivery, and malformations (Gortzak-Uzan et al 2001). The pregnancy experience often impacts the psychological development of teenagers as well.…”
Section: Consequences Of Teen Pregnancymentioning
confidence: 99%